2017
DOI: 10.1039/c7ra11291b
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation reaction of B2H6 on TiN surfaces during atomic layer deposition: first-principles study

Abstract: In the fabrication process of memory devices, a void-free tungsten (W) gate process with good conformability is very important for improving the conductivity of the W gate, leading to enhancement of device performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…In our previous study, 19 we reported that these severe problems, such as seam or void, in filling the W metal gate for memory devices would be attributed to the difference of deposition rate of W film depending on the orientations of TiN surfaces by analyzing dissociation reaction of B 2 H 6 on three different TiN surfaces, such as TiN (001), Ti-terminated TiN (111), and N-terminated TiN (111) using density functional theory (DFT) calculation method. Since this previous study gives only information for B 2 H 6 dosing process, we want to report how important the understanding of the overall ALD reaction mechanism could be for improving W deposition process.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In our previous study, 19 we reported that these severe problems, such as seam or void, in filling the W metal gate for memory devices would be attributed to the difference of deposition rate of W film depending on the orientations of TiN surfaces by analyzing dissociation reaction of B 2 H 6 on three different TiN surfaces, such as TiN (001), Ti-terminated TiN (111), and N-terminated TiN (111) using density functional theory (DFT) calculation method. Since this previous study gives only information for B 2 H 6 dosing process, we want to report how important the understanding of the overall ALD reaction mechanism could be for improving W deposition process.…”
Section: Introductionmentioning
confidence: 84%
“… 22 Three different planes of TiN surfaces, TiN (001), Ti-terminated TiN (111), and N-terminated TiN (111) can be generated because poly-crystalline TiN layers with (001) and (111) preferred orientations were mainly observed in deposition of TiN films. 23,24 Our previous results 19 imply that B-covered surface can be generated very well by B 2 H 6 flow especially on N-terminated TiN (111) surface rather than other TiN surfaces due to even higher reactivity of B 2 H 6 on the former than the latter.…”
Section: Introductionmentioning
confidence: 91%
“…As a surface self-limiting chemisorption reaction, the higher the active sites on the surface exit, the greater the chemisorption probability is, and the better the surface nucleation. Hwanyeol Park et al [ 163 ] simulated the process of ALD W deposited on TiN surface using B 2 H 6 and WF 6 as precursors by first-principles density functional theory (DFT). The precursor adsorption processes of ALD W on different TiN surfaces were investigated in detail.…”
Section: Ald W For Nano-transistorsmentioning
confidence: 99%
“…30,31 This method was made to search one of the various states near the transition-state along the reaction path, converging at the highest saddle point. [32][33][34][35] Fig. 1 shows the nal atomic structures of 64 C atom-containing a-C lms with an increase in the atomic density (3.2 to 4.0 g cm À3 ) and hydrogen concentrations (15.6 to 31.2 at%).…”
Section: Dft Calculationsmentioning
confidence: 99%